Comparison of clinicopathological features and prognosis of papillary thyroid carcinoma and microcarcinoma: A population-based propensity score matching analysis - Qian, Bei; Hu, Longqing; Zhang, Shoupeng; Zhu, Junlin; Mei, Li; Huang, Tao; Qu, Xincai (Frontiers in Endocrinology, 2022)
Background: Overtreatment of papillary thyroid microcarcinoma (PTMC) has become a common concern. This study aimed to compare clinicopathological features between PTMC and papillary thyroid carcinoma (PTC), and to explore whether surgery can confer significant survival benefits in all patients with PTC or PTMC. Methods: Data of 145951 PTC patients in SEER database and 8751 PTC patients in our institution were retrospectively collected. Patients with tumors less than 10 mm in diameter were classified as PTMC cohort, and the rest were PTC cohort. Clinicopathological features between PTMC and PTC were compared based on SEER cohort, and validated by institutional data. Survival analysis was conducted to explore the effect of surgery on the prognosis of patients. Propensity score matching (PSM) analysis was applied to adjust for potential confounders and bias to match more comparable cohorts. Results: Compared with PTC, PTMC exhibited the following characteristics: more common in female and whites, older age at diagnosis, lower proportion of follicular variants, intraglandular dissemination, extratglandular invasion and capsular invasion and higher proportion of multifocality, fewer lymph node and distant metastases, and higher cancer-specific survival (CSS) and overall survival (OS; all P value<0.05). As for treatment, PTMC patients had a lower proportion of radiotherapy, chemotherapy and total thyroidectomy, while a higher proportion of lobectomy and/or isthmectomy. There was no significant difference in CSS for PTMC patients staged T1N0M0 with or without surgery (P=0.36). Conclusion: Generally, PTMC showed higher biological indolence than PTC, which meant a higher survival rate for patients in both OS and CSS. For PTMC patients staged T1N0M0, Active surveillance (AS) may be a potentially feasible management strategy. However, the maintenance of good medical compliance and the management of psychological burden cannot be ignored for the patients included in AS.